A Stochastic Programming Model for Commercial Bank Bond Portfolio Management - Crane, Dwight B. (Journal of Financial and Quantitative Analysis, 1971)
This paper presents a discrete stochastic programming model for commercial bank bond portfolio management. It differs from previous bond portfolio models in that it provides an optimization technique that explicitly takes into consideration the dynamic nature of the problem and that incorporates risk by treating future cash flows and interest rates as discrete random variables. The model's data requirements and its computational demands are sufficiently limited so that it can be implemented as a normative aid to bond portfolio management. In addition, it can be extended by the addition of other asset and liability categories to serve as a more general model for commercial bank asset and liability management.